1999
DOI: 10.1007/bf02560510
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus serotypes and sources of infection in patients with HCV-related chronic liver disease from one geographical Area in southeast Italy

Abstract: Hepatitis C virus serotypes and sources of infection in HCV-positive patients from a restricted geographical area were evaluated. HCV serotypes were determined by Murex serotyping assay. Of 192 samples, serotypes were detected in 189 (98.5%): type 1 proved to be the most common (53.1%), followed by types 2 (15.2%), 3 (6.2%), 6 (5.3%), 4 (3.6%) and 5 (1.6%). Intravenous drug users were significantly younger than the rest of the patients and infected mainly with HCV type 3. Transmission of HCV 3 has only been ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…Data from the present study also confirm previous observations that HCV genotype 3a is more frequently found in IDUs [11,12] and that PBMC infection with HCV does not correlate with virus load or HCV genotype [5,13]. In particular, even though a higher percentage of genotype 1 was found in infected cells, the rate reflects the distribution of HCV genotypes in a population of Italian adults with HCV infection.…”
Section: Discussionsupporting
confidence: 92%
“…Data from the present study also confirm previous observations that HCV genotype 3a is more frequently found in IDUs [11,12] and that PBMC infection with HCV does not correlate with virus load or HCV genotype [5,13]. In particular, even though a higher percentage of genotype 1 was found in infected cells, the rate reflects the distribution of HCV genotypes in a population of Italian adults with HCV infection.…”
Section: Discussionsupporting
confidence: 92%
“…Distribution of HCV genotypes in our patients followed the prevalence map described by Simmonds [5] showing a higher frequency of subtype 1b in Spain. However, genotype distribution by epidemiological groups revealed significantly higher percentages of subtype 1a and genotype 3 among intravenous drug users in agreement with reports from south‐east [15] and northern [16] Italy, France [17,18], north‐east of England [19], southern Spain [20], and overall in western European countries for genotype 3 [2]. According to the year at which HCV infection was probably acquired, we found that the onset of intravenous drug addiction in our country was associated with entry of new HCV genotypes because after 1970 – the year at which the first case of HCV infection was observed – subtype 1a and genotypes 3 and 4 began to be detected among HCV‐infected patients with history of transfusion.…”
Section: Discussionsupporting
confidence: 90%
“…Sixty‐six were excluded for the following reasons. Nine articles failed to give the exact number of IVDUs enrolled [7–15]; seven papers, which concerned several risk groups including IVDUs, gave no separate prevalence rates for IVDUs [16–22]; sixteen papers reported on specific subpopulations of IVDUs (HIV‐seropositive IVDUs, IVDUs with acute hepatitis or deceased IVDUs) [23–38]. In three reports it was not specified if the enrolled drug users consisted of IVDUs alone or of both non‐IVDUs and IVDUs [39–41]; in 11 studies the number of IVDUs enrolled was less than 50 [42–51].…”
Section: Resultsmentioning
confidence: 99%